2016
DOI: 10.17795/ijcp-5494
|View full text |Cite
|
Sign up to set email alerts
|

The Dual Nature of Iron in Relation to Cancer: A Review

Abstract: Background: Although iron is essential for all cells, it could be potentially hazardous. This is mostly due to iron participation in oxidation-reduction reactions. In terms of cancer risk, the role of both iron deficiency and overload can be studied in two directions, protective or therapeutic effects, and carcinogenic effects. Materials and Methods:PubMed, Science direct, Ovid, Proquest, Medline, and Google scholar databases were used to obtain articles identified by using the key words "Iron", "Iron deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 164 publications
0
5
0
Order By: Relevance
“…Therefore, regulation of iron levels is crucial for proper cell functioning . Both iron overload and its deficiency may play important roles in the mechanisms of carcinogenesis. Schonberg et al . observed that stem-like GBM cells are characterized by increased iron uptake compared to the remaining GBM and normal brain cells, and this mechanism may affect tumor proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, regulation of iron levels is crucial for proper cell functioning . Both iron overload and its deficiency may play important roles in the mechanisms of carcinogenesis. Schonberg et al . observed that stem-like GBM cells are characterized by increased iron uptake compared to the remaining GBM and normal brain cells, and this mechanism may affect tumor proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Second, dietary or cellular iron has a double nature in relation to tumorigenesis. Either iron deficiency or over sufficiency may cause cellular stresses, thus altering the autophagic status even cell death [ 41 , 42 ]. Cancer cells develop a dependence on iron well over that of their non-malignant counterparts, which is termed as “iron addiction” [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The estimated prevalence of obesity-associated cancers is 684,000 US annually, including 210,000 among men and 470,000 among women, per CDC data. The evidence of obesity-associated cancers is consistent with breast cancer in postmenopausal women, adenocarcinoma of the esophagus, colon, endometrium, gall bladder, gastric, renal cell, pancreas, thyroid, meningioma, and multiple myeloma [15,16].…”
Section: Introductionmentioning
confidence: 88%